PENDAMPINGAN PENGAYAAN BIOLOGI BAGI SISWA SMA NEGERI 4 JAYAPURA - Maria Ludia Simonapendi; Suharno Suharno; Puguh Sujarta (JURNAL PENGABDIAN PAPUA, 2022)
Recently, SMAN 4 Jayapura is the only one high school in Jayapura which implemented aaccelerate program for their student. The pupils included into this program should complete their studies within two years, which is one year earlier than common pupils. The problems rising from this program was with limited times (2 years) the student should accomplish all the same theory with regular class, which means they have to have extra class to finish it. Therefore, our team was ofering the solution to be an assistant for their extra class. The extra class was given after school hours, start from 3pm to 5pm once a week. The result of our assistance, the student can complete all the theory within times given and from total 28 students 10 of them have choosen biology and its apllied for their major in University.Keywords: :  accelerate class; biology; assistant; SMAN 4 Jayapura school